European Intelligence Community – the unfulfilled pillar of the European Union (Economic and Political Thought, 2016)
Taking into account wider autonomous competences at the Europeanlevel and the appreciation of the information phenomenon – the need fora redefinition of the role, function and place of intelligence is outlined (notonly in the structure of the state but also in the global transnational alliances).Europe needs a common sense of security, unified threat perception,and thus joint risk assessments. For this reason, the EU must providea framework for intensifying cooperation, at least by developing intelligencecommunity – matched with declared political ambitions of Europe. The questionis whether the EU needs specially dedicated intelligence agencies inthis regard, or if intuitions operating at the level of the EU and the MemberStates are sufficient. And if so, which agencies – and how constructed andcommunitarised. If the European Common Intelligence Policy cannot betreated in institutional terms, it is only because of the lack of political will.Obstacles are among others: lack of trust, finances, loss of foreign partners,technical and logistical issues, legal and institutional aspects, cultural differences,politics and ideology. In the case of a change of political will, andpreparing proposals for solutions, one can talk about the extension of thecurrent model retaining the status quo or an increased cooperation model, ora model of full European intelligence with the European Intelligence Agencyat the helm.